Human Capital and Institutional Capacity as Drivers of Local Revenue Efficiency: Evidence from Tanzanian Local Government Authorities - Dennis Hyera; Dickson Pastory; Philipina Kiwala (International Journal of Management, Accounting and Economics)
Local Government Authorities (LGAs) in Tanzania are central to mobilizing own-source revenues, which are essential for financing local development and delivering public services, yet many continue to underperform despite reforms such as the Local Government Finance Act (1982, revised 2010) and adoption of electronic revenue collection systems, collecting on average only 65–70% of their projected revenue potential (PO-RALG, 2022; URT, 2019). This study investigates the role of human capital and institutional capacity in enhancing revenue efficiency across 24 LGAs over the period 2016/17 to 2022/23, employing a Panel Data Regression Model to capture both cross-sectional and temporal variations in revenue performance determinants. Human capital is measured through staff qualifications, experience, and frequency of training, while institutional capacity encompasses digital revenue systems, internal control mechanisms, and organizational structures, drawing on resource-based and institutional theory perspectives (Barney, 1991; Musgrave, 2019). Results indicate that LGAs with higher proportions of qualified staff and regular training programs achieve revenue efficiency gains of up to 15%, whereas weak internal controls and outdated systems reduce efficiency by 10–12%; further, implementation of digital tax platforms and strengthened audit mechanisms is associated with statistically significant improvements of 8–9% (p < 0.01). Based on these findings, the study recommends targeted human resource development, continuous professional training, modernization of institutional frameworks, and investment in digital revenue management to sustain local revenue growth. These insights provide evidence-based guidance for policymakers and local administrators seeking to optimize revenue mobilization, strengthen fiscal autonomy, and enhance service delivery within Tanzania’s decentralized governance framework.